DEVELOPING WEB-BASED TUTORIAL VIDEO LEARNING MEDIA TO IMPROVE STUDENTS ONLINE MARKETING LEARNING OUTCOME AT SMK NEGERI SUKOHARJO - Dwi Hendra Kusuma; Trisno Martono; Dewi Kusuma Wardani (Department of Economics Education, Universitas Sebelas Maret, 2018)
The aim of this research is to develop learning media using Online Marketing Video Learning Information System technology which can be accessed online, and improve the learning outcomes in Online Marketing learning at Vocational High School in Sukoharjo. The method used in this research is Research and Development methods that apply the media to students in grade X of Marketing Vocational High School, Sukoharjo especially in online marketing program. The research was examined by procedure steps of preliminary research, development and testing steps. The steps of video development cover collecting material, making storyboard, surveying, producing media, and applying media. The information system development steps involve Communication, Planning, Modelling, Construction and Deployment. Data analysis techniques applied in this research is a simple descriptive analysis. The research compares between the Pre test and Post test result to find out the result of study. This research was expected to increase the result of study in Online Marketings learning.